Aqueous antifoam agent, process for its preparation and method for defoaming
Patent Information
- Application Number
- CN202611488259.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]本发明的主要目的在于提供水性消泡剂及其制备方法和消泡方法,解决现有技术中消泡剂存在分散性差、耐高温性能不足、难以适应超白光伏玻璃的技术问题
本发明的水性消泡剂的纳米颗粒中的钛和硅通过共价键Ti–O–Si结合,粒径为1nm~30nm,在水性体系中可以稳定分散,使水性消泡剂形成含溶胶颗粒的溶胶体系,将消泡剂用于玻璃熔制阶段的消泡处理,其活性组分能够在玻璃液中瞬时均匀扩散,进行无死角消泡,同时不会在成品玻璃中产生白点、结石等杂质缺陷,能够保障超白光伏玻璃级别的玻璃的高透光率与外观品质,避免了使用传统的钛粉进行消泡因钛粉颗粒团聚导致的消泡效果差、成品玻璃瑕疵多、透光率差等问题。
Smart Images

Figure CN122977690A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of defoamers for glass, and more particularly to an aqueous defoamer, its preparation method, and defoaming method. Background Technology
[0002] Ultra-clear photovoltaic glass is a special silicate glass characterized by low iron, high silicon, and high light transmittance, serving as a key encapsulation material for photovoltaic modules. Its melting quality directly determines the photoelectric conversion efficiency and service life of the photovoltaic module. During the melting process of this type of glass (typically at 1400~1500℃), the high silicon formulation results in high melt viscosity. Combined with the decomposition of carbonates and other components in the batch and melt convection, a dense and stable foam layer continuously forms on the surface of the molten glass.
[0003] This foam layer severely hinders the transfer of heat from the furnace flame to the molten glass, leading to decreased furnace thermal efficiency, increased energy consumption, and accelerated erosion of the furnace refractory materials, thus shortening the furnace's lifespan. Therefore, efficiently eliminating surface foam in molten glass is a key technical challenge for the photovoltaic glass industry to achieve energy conservation, emission reduction, and improved product quality.
[0004] Currently, the high-temperature defoaming technology used in the industry has the following main drawbacks: Traditional titanium dioxide powder defoamers suffer from poor dispersibility: products with titanium dioxide powder as the active component tend to agglomerate, making them difficult to disperse evenly in molten glass. These agglomerates not only lead to poor localized defoaming effects but can also form defects such as white spots and inclusions in the finished glass product, compromising the high light transmittance and high purity characteristics of photovoltaic glass.
[0005] Silicone and polyether defoamers have insufficient temperature resistance: These defoamers are typically used at temperatures not exceeding 400℃, and will rapidly decompose and fail under ultra-high temperature conditions exceeding 1400℃ in photovoltaic melting furnaces. The free carbon and inorganic impurities in the decomposition products will contaminate the molten glass, leading to quality problems such as decreased light transmittance and color difference.
[0006] Solvent-based titanium-based defoamers pose safety hazards and environmental pollution: To solve powder dispersion problems, some titanium-based defoamers use flammable organic solvents such as kerosene and solvent oil as dispersion media. The resulting products have low flash points, are flammable and explosive, and are classified as hazardous chemicals, posing high safety risks during storage, transportation, and use. Furthermore, they release large amounts of VOCs at high temperatures, failing to meet the requirements for green and environmentally friendly safe production.
[0007] General-purpose defoamers lack targeted design: Commercially available general-purpose glass defoamers have not been optimized for the specific formulation system and high-temperature foaming mechanism of ultra-white photovoltaic glass, which is characterized by "high silicon, low iron, and high purity". As a result, the defoaming effect is limited and it is difficult to fundamentally solve its unique foaming problem.
[0008] In summary, existing technologies lack a dedicated water-based high-temperature defoamer that can precisely adapt to ultra-white photovoltaic glass formulations, stably defoam at ultra-high temperatures, exhibit excellent dispersion performance, and is safe, environmentally friendly, and free of impurities. Therefore, developing a defoamer that can solve the above-mentioned technical problems and its preparation method has significant industrial application value and market prospects. Summary of the Invention
[0009] The main objective of this invention is to provide an aqueous defoamer and its preparation and defoaming methods, thereby solving the technical problems of poor dispersibility, insufficient high-temperature resistance, and difficulty in adapting to ultra-white photovoltaic glass in existing defoamers.
[0010] To achieve the above objectives, the present invention provides an aqueous defoamer comprising nanoparticles, wherein the nanoparticles have a particle size range of 1 nm to 30 nm and contain Ti–O–Si covalent bonds. The nanoparticles are obtained by reacting titanate, silane coupling agent, complexing agent, and deionized water. The complexing agent includes at least one of acetylacetone, triethanolamine, diethanolamine, ethylene glycol, propylene glycol, and diethylene glycol. The titanate and the complexing agent undergo a complexation reaction to obtain a complex. The complex and the silane coupling agent undergo a co-hydrolysis reaction in the presence of deionized water to produce titanium-containing hydrolysis products and silicon-containing hydrolysis products. The titanium-containing hydrolysis product and the silicon-containing hydrolysis product undergo a condensation reaction to obtain an aqueous defoamer containing the nanoparticles.
[0011] In some embodiments of the present invention, the general reaction formula for the complexation reaction is as follows:
[0012] The general reaction formula for the hydrolysis reaction is as follows:
[0013] The general reaction formula for the condensation reaction is as follows:
[0014] The titanate refers to the titanium ester, where R is -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; Refers to the complexing agent, where n is an integer greater than 0 and less than or equal to 2; Refers to the complex; Referring to the silane coupling agent, It is -CH3 or -CH=CH2. It is -CH3 or -CH2CH3; ; Refers to the titanium hydrolysis products; Refers to the silicon hydrolysis products mentioned above; Refers to the nanoparticles.
[0015] In some embodiments of the present invention, the titanate includes at least one of tetraisopropyl titanate, tetra-n-butyl titanate, and tetraisobutyl titanate. And / or, the silane coupling agent includes at least one of methyltrimethoxysilane, methyltriethoxysilane, or vinyltriethoxysilane.
[0016] In some embodiments of the present invention, based on a total mass of 100 parts, the titanate ester is 7-15 parts, the silane coupling agent is 3-6 parts, the complexing agent is 5-15 parts, and the balance is the deionized water.
[0017] In some embodiments of the present invention, the aqueous defoamer further includes an aqueous dispersion stabilizer, which is 1 to 3 parts by weight.
[0018] In some embodiments of the present invention, the aqueous dispersion stabilizer includes at least one of polyacrylate, sodium hexametaphosphate, sodium pyrophosphate, and polyvinylpyrrolidone; and / or, calculated by weight, the aqueous dispersion stabilizer is 1 to 3 parts.
[0019] The present invention also provides a method for preparing the aqueous defoamer as described above, the method comprising the following steps: Complexation reaction: Titanate and silane coupling agent are mixed and a complexing agent is added, and the mixture is stirred to obtain a complexed modified precursor; Co-hydrolysis and condensation reaction: Deionized water is added dropwise to the complexed modified precursor, and a co-hydrolysis and condensation reaction is carried out under heating and stirring conditions to obtain an aqueous defoamer containing nanoparticles.
[0020] In some embodiments of the present invention, the temperature of the stirring reaction is 30°C to 40°C, and the reaction time is 90 min to 120 min.
[0021] In some embodiments of the present invention, the reaction temperature of the co-hydrolysis and condensation reaction in the co-hydrolysis and condensation reaction steps is 35°C to 55°C.
[0022] In some embodiments of the present invention, the preparation method further includes the following steps: Dispersion: Add an aqueous dispersing stabilizer to the aqueous defoamer containing nanoparticles.
[0023] The present invention also provides a defoaming method for use in glass manufacturing processes, comprising the following steps: during the glass melting stage, spraying the water-based defoamer as described above onto the foam on the surface of the molten glass.
[0024] The beneficial effects that this invention can achieve are: The nanoparticles of the water-based defoamer of this invention are bonded by covalent bonds Ti–O–Si, with a particle size of 1nm~30nm. They can be stably dispersed in an aqueous system, forming a sol system containing sol particles. When the defoamer is used for defoaming treatment in the glass melting stage, its active components can diffuse instantly and uniformly in the glass melt, achieving defoaming without dead angles. At the same time, it will not produce impurities such as white spots or stones in the finished glass, ensuring high light transmittance and appearance quality of ultra-white photovoltaic glass. This avoids the problems of poor defoaming effect, many defects in finished glass, and poor light transmittance caused by the agglomeration of titanium powder particles when using traditional titanium powder for defoaming.
[0025] Furthermore, the titanium-based component in the water-based defoamer of this invention is ultimately transformed into nano-TiO2 during the defoaming process. Nano-TiO2 exhibits high-temperature resistance of ≥1500℃, maintaining structural stability, without decomposition or deactivation even under photovoltaic melting furnace conditions of 1400~1500℃. The introduction of the silicon-based component further enhances the interfacial compatibility between the active component and the silicate glass melt. The synergistic effect of both components rapidly breaks down the dense foam layer and inhibits foam regeneration, solving the technical problems of high-temperature pyrolysis failure and glass melt contamination associated with traditional organosilicon and polyether defoamers.
[0026] Furthermore, the water-based defoamer of the present invention uses deionized water as the reaction medium and the final dispersion carrier, does not rely on flammable organic solvents such as kerosene and solvent oil, the system as a whole is non-flammable and has no risk of flammability or explosion, is not a hazardous chemical, and does not release a large amount of VOCs during use, which meets the green and safe production requirements of the photovoltaic industry.
[0027] Furthermore, the silicon-based component in the water-based defoamer of the present invention is homologous to the photovoltaic glass matrix (high silicate system). The Ti–O–Si covalent bond structure gives it excellent compatibility with the glass melt. The defoaming process is gentle and does not interfere with the original glass formulation and melting process. It achieves precise matching of the high-temperature foaming mechanism of ultra-white photovoltaic glass and fills the technical gap of special defoamers in the field of photovoltaic glass. Attached Figure Description
[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0029] Figure 1 This is a schematic flowchart of a method for preparing an aqueous defoamer according to the present invention; Figure 2 The particle size distribution diagrams are shown for the water-based defoamers in Examples 1 to 3 of this invention.
[0030] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0031] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0033] In this invention, descriptions involving "first," "second," etc., are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. Furthermore, the technical solutions of the various embodiments can be combined with each other, but only on the basis of being achievable by those skilled in the art. If the combination of technical solutions is contradictory or impossible to implement, such a combination should be considered non-existent and not within the scope of protection claimed by this invention.
[0034] This invention provides an aqueous defoamer comprising nanoparticles with a particle size ranging from 1 nm to 30 nm and containing Ti–O–Si covalent bonds.
[0035] The nanoparticles of this invention are obtained by reacting titanate, silane coupling agent, complexing agent, and deionized water. The complexing agent includes at least one selected from acetylacetone, triethanolamine, diethanolamine, ethylene glycol, propylene glycol, and diethylene glycol. Specifically, the titanate and the complexing agent undergo a complexation reaction to obtain a complex. The complex and the silane coupling agent then undergo a co-hydrolysis reaction in the presence of deionized water to produce titanium-containing hydrolysis products and silicon-containing hydrolysis products. The titanium-containing hydrolysis products and the silicon-containing hydrolysis products undergo a condensation reaction to obtain an aqueous defoamer containing nanoparticles.
[0036] This invention utilizes a complexing agent to induce a complexation reaction between the complexing agent and the titanate ester, effectively reducing the hydrolytic activity of the titanate ester. This allows the complexed titanate ester and silane coupling agent to achieve controlled co-hydrolysis and directional condensation. Unlike traditional disordered co-hydrolysis processes, this invention generates a titanium-silicon composite sol structure containing Ti–O–Si covalent bonds in situ, enabling uniform bonding of the titanium and silicon phases at the molecular level. This yields nanoparticles with a particle size range of 1nm to 30nm, precisely controlling the microscopic size of the nanoparticles in the aqueous defoamer. This allows the nanoparticles to exist stably in a monodisperse state in the aqueous system for a long time, preventing agglomeration and exhibiting excellent storage stability. This fundamentally inhibits the agglomeration of nanoparticles and significantly improves the dispersion uniformity of the system.
[0037] The addition of silane coupling agents enables controlled co-hydrolysis and directional condensation reactions with the complexed titanate, forming Ti–O–Si covalent bonds at the molecular level, thereby uniformly introducing silicon-based components into the titanium-based network. The introduction of silicon-based components can, on the one hand, effectively inhibit the aggregation of nanoparticles and significantly improve the storage stability of the water-based defoamer; on the other hand, it can enhance the interfacial compatibility between the active components in the water-based defoamer and the silicon-based glass melt, allowing the defoamer to act rapidly and uniformly on the foam layer on the surface of the molten glass at high temperatures, while avoiding glass defects caused by component incompatibility.
[0038] Deionized water directly participates in the co-hydrolysis reaction of titanate and silane coupling agent, converting alkoxy groups into hydroxyl groups, providing the necessary prerequisite for the subsequent condensation to form Ti–O–Si covalent bonds; secondly, as a reaction medium, deionized water provides a homogeneous environment for the co-hydrolysis and condensation reactions, regulates the reaction rate, and ensures the uniform generation of nanoparticles; in addition, deionized water also serves as the main dispersion carrier for the final product, enabling the nanoparticles to be stably dispersed in the aqueous defoamer, forming a uniform and non-flammable aqueous sol system.
[0039] In some embodiments, the conductivity of deionized water is ≤10μS / cm, which ensures that the water-based defoamer is free of metal ions and impurities, meeting the stringent requirements for high purity of ultra-white photovoltaic glass.
[0040] In some embodiments, the general reaction formula for the complexation reaction is as follows: In the general reaction formula Refers to the titanate ester, n Refers to the complexing agent, The complex referred to here, R is -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2, and n is an integer greater than 0 and less than or equal to 2, for example 2 to 6, which can be 1, 2, 3, 4, 5, 6, etc.
[0041] In some embodiments, the general reaction formula for the hydrolysis reaction is as follows: In the general reaction formula Refers to silane coupling agents, It is -CH3 or -CH=CH2. It is -CH3 or -CH2CH3. Refers to deionized water, the molar amount of water is determined by n; The titanium hydrolysis product obtained after hydrolysis of the reference complex. This refers to the silicon hydrolysis product obtained after hydrolysis of a silane coupling agent.
[0042] In some embodiments, the general reaction formula for the condensation reaction is as follows: In the general reaction formula Refers to nanoparticles, which are uniformly dispersed in an aqueous defoamer. During the glass melting stage, the aqueous defoamer is sprayed onto the foam layer to achieve the defoaming effect.
[0043] In some embodiments, the titanate includes at least one of tetraisopropyl titanate, tetra-n-butyl titanate, and tetraisobutyl titanate. The above-mentioned titanates, as titanium sources, can bond with hydrolyzed silane coupling agents after complexation and passivation to form nanoparticles with uniform particle size and stable activity, thereby forming a colloidal aqueous defoamer.
[0044] Preferably, the titanate is tetraisopropyl titanate, which has moderate activity and strong controllability of hydrolysis. After complexation treatment with a complexing agent, it can achieve mild hydrolysis.
[0045] In this invention, the complexing agent includes at least one of acetylacetone, triethanolamine, diethanolamine, ethylene glycol, propylene glycol, and diethylene glycol. The titanate can complex with the above-mentioned complexing agents before subsequent hydrolysis. The complexing effect can passivate the active sites of the titanate, inhibit the violent hydrolysis of the titanate, and make the hydrolysis and condensation processes controllable, thereby enabling controllable particle size of the water-based defoamer nanoparticles.
[0046] In some embodiments, acetylacetone, triethanolamine, and diethylene glycol are used as the main complexing components to passivate the active sites of titanate esters through strong coordination and inhibit violent hydrolysis. Ethylene glycol and propylene glycol are used as auxiliary components to finely regulate the reaction rate and prevent particle size runaway.
[0047] In some embodiments, the silane coupling agent includes at least one of methyltrimethoxysilane, methyltriethoxysilane, or vinyltriethoxysilane. After hydrolysis, the above silane coupling agent can undergo controlled co-hydrolysis and controlled condensation reaction with the complexed titanate to obtain a water-based defoamer with controllable, uniform, and non-agglomerated particle size. This effectively optimizes the morphology of nano-sol particles, inhibits particle agglomeration, significantly improves the storage stability of the system, and enhances the interfacial compatibility between the active component and the silicon-based glass melt.
[0048] This invention can stabilize and regulate the microscopic size of nanoparticles in water-based defoamers by controlling the amount of titanate, silane coupling agent, complexing agent, and deionized water used, thereby inhibiting nanoparticle aggregation from the source and improving the dispersion uniformity of the system.
[0049] Therefore, in some embodiments, based on a total mass of 100 parts, the titanate is 7-15 parts, the silane coupling agent is 3-6 parts, the complexing agent is 5-15 parts, and the balance is deionized water.
[0050] For example, the titanate ester can be 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.
[0051] For example, the silane coupling agent can be 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, etc.
[0052] For example, the complexing agent may be 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts, 14.5 parts, 15 parts, etc.
[0053] In some embodiments, the present invention also introduces an aqueous dispersion stabilizer. The aqueous dispersion stabilizer can be uniformly adsorbed on the surface of nanoparticles through a dual stabilization mechanism of electrostatic adsorption and steric hindrance. It can effectively counteract the charge on the surface of nanoparticles, prevent mutual adsorption and agglomeration and sedimentation between particles, thereby further improving the system uniformity and long-term storage stability of the aqueous defoamer, ensuring that the product does not separate, precipitate, or degrade in performance during long-term storage.
[0054] In some embodiments, based on a total mass of 100 parts, the components are: 7-15 parts titanate, 3-6 parts silane coupling agent, 5-15 parts complexing agent, 1-3 parts aqueous dispersion stabilizer, and the remainder is deionized water.
[0055] For example, the aqueous dispersion stabilizer may be 1 part, 2 parts, or 3 parts.
[0056] In some embodiments, the aqueous dispersion stabilizer includes at least one of polyacrylate, sodium hexametaphosphate, sodium pyrophosphate, and polyvinylpyrrolidone. These types of aqueous dispersion stabilizers can be uniformly adsorbed onto the surface of nanoparticles through a dual stabilization mechanism of electrostatic adsorption and steric hindrance. This effectively counteracts the surface charge of the particles, prevents mutual adsorption and agglomeration between particles, further improves the uniformity and long-term storage stability of the sol system, and ensures that the product does not separate, precipitate, or experience performance degradation during long-term storage.
[0057] The present invention also provides a method for preparing the water-based defoamer as described above, referring to... Figure 1 The preparation method includes the following steps: S10, Complexation reaction: Titanate ester and complexing agent are mixed and silane coupling agent is added, and the mixture is stirred to obtain complexed modified precursor; S20, Co-hydrolysis and condensation reaction: Deionized water is added dropwise to the complex-modified precursor, and a co-hydrolysis and condensation reaction is carried out under heating and stirring conditions to obtain an aqueous defoamer containing nanoparticles.
[0058] In some embodiments, during the complexation reaction step, the temperature of the stirring reaction is 30°C to 40°C, and the reaction time is 90 min to 120 min. Exemplarily, the temperature of the stirring reaction can be 30°C, 32°C, 35°C, 38°C, 40°C, etc., and the reaction time can be 90 min, 100 min, 110 min, 120 min, etc. Under these temperature conditions, it is beneficial to promote the complexation and coordination of the complexing agent with Ti in the titanate, occupying some of the active sites of the titanate, passivating the transient hydrolysis activity of the titanate, and fundamentally preventing problems such as excessively high rates and agglomeration precipitation during subsequent co-hydrolysis, thus providing a core guarantee for subsequent uniform and controllable hydrolysis.
[0059] In some embodiments, the stirring speed of the stirring reaction is 100 rpm to 200 rpm.
[0060] In some embodiments, the titanate and the complexing agent are first mixed and stirred at 25°C to 30°C for 20 to 35 minutes to promote the complexation reaction. Subsequently, the silane coupling agent is added in batches and mixed thoroughly.
[0061] In some embodiments, the reaction temperature of the co-hydrolysis reaction and the condensation reaction is 35℃~55℃, which can be 35℃, 38℃, 40℃, 42℃, 45℃, 48℃, 50℃, 52℃, 55℃, etc. This temperature range can ensure that the co-hydrolysis reaction proceeds at a uniform and slow rate, avoiding both incomplete hydrolysis at low temperatures and excessively large nanoparticle size caused by violent reactions at high temperatures.
[0062] In some embodiments, during the co-hydrolysis and condensation reaction steps, the complex-modified precursor is heated to 35°C to 55°C, deionized water is added dropwise, and the co-hydrolysis reaction is carried out within this temperature range.
[0063] In some embodiments, the preparation method further includes the following step: S30, dispersion: adding an aqueous dispersion stabilizer to an aqueous defoamer containing nanoparticles.
[0064] In some embodiments, the dispersion step specifically includes: slowly heating the hydrolyzed reaction system to 50°C~60°C at a rate of 1°C~2°C / min; adding a pre-prepared aqueous dispersion stabilizer; adjusting the stirring speed to 250rpm~350rpm; and continuously stirring for 30min~40min to allow the aqueous dispersion stabilizer to fully dissolve and uniformly adsorb onto the surface of the nanoparticles.
[0065] In some embodiments, the preparation method includes the following steps: filtering the aqueous defoamer through a 0.22μm filter to remove trace amounts of large particulate impurities and a small amount of unreacted residues in the system; loading the filtered qualified finished product into a sealed and corrosion-resistant container and storing it in a cool and dry environment to maintain stable performance, without stratification or precipitation for a long time.
[0066] The water-based defoamer of this invention has a high temperature resistance of ≥1500℃. It is structurally stable, does not decompose, does not deactivate, and does not volatilize under ultra-high temperature conditions of 1400~1500℃ in photovoltaic melting furnaces. It is suitable for glass manufacturing processes and is used to eliminate foam on the surface of molten glass.
[0067] Therefore, the present invention further provides a defoaming method, comprising the following steps: during the glass melting stage, spraying an aqueous defoamer onto the foam on the surface of the molten glass for defoaming treatment.
[0068] By injecting an aqueous defoamer into the furnace, nano-TiO2 and SiO2 particles are generated in situ on the surface of the molten glass under high-temperature conditions. These particles preferentially adsorb onto the microbubble interfaces on the molten glass surface, disrupting the stable surface tension structure of the bubbles and causing them to rupture in the early stages. This continuous disruption of microbubbles on the molten glass surface inhibits foam layer formation, thereby improving the clarification efficiency and light transmittance of the molten glass, and ultimately enhancing the clarification effect and the quality of the finished glass product. Furthermore, since both TiO2 and SiO2 are components of glass, the aqueous defoamer does not introduce additional impurities in the high-temperature furnace and does not affect the glass's light transmittance or chemical stability.
[0069] The water-based defoamer of the present invention has the advantages of excellent dispersibility, stable defoaming performance at ultra-high temperature, safety and environmental protection, and homology with the glass matrix. It is especially suitable for high-silicon, low-iron, and high-purity formulation systems of ultra-white photovoltaic glass.
[0070] Therefore, in some embodiments, the aqueous defoamer of the present invention is used in the photovoltaic glass manufacturing process, and the defoaming method is used in the photovoltaic glass manufacturing process.
[0071] In some embodiments, the photovoltaic glass comprises the following components by mass percentage: silicon dioxide (SiO2) 72.1%~72.4%, aluminum oxide (Al2O3) 0.8%~1.2%, calcium oxide (CaO) 8.5%~8.9%, magnesium oxide (MgO) 3.7%~4.1%, alkali metal oxides (Na2O+K2O) 13.2%~13.6%, titanium dioxide (TiO2) 0.009%~0.016%, sulfur trioxide (SO3) 0.15%~0.29%, antimony trioxide (Sb2O3) ≤0.1%, and ferric oxide (Fe2O3) ≤0.010%. This component range covers the industrial production fluctuation range of this high-end ultra-clear photovoltaic glass structure. The component system is stable, has excellent light transmission performance, and is more versatile and adaptable, fully covering the similar formulation systems of mainstream photovoltaic cover glass.
[0072] In some embodiments, the defoaming method is tailored to the furnace structure and foam aggregation characteristics of large-scale ultra-white photovoltaic glass melting furnaces with a capacity of 1200 tons / day or more. Multiple pairs of spray guns are used in conjunction with natural gas injection to directly target the densest and thickest area of the foam layer formed by the thermal decomposition of the batch material. After the aqueous defoamer concentrate is injected into the high-temperature furnace at high speed along with the natural gas flame, the moisture and organic components in the system rapidly vaporize and fully combust and decompose under high-temperature conditions, ultimately being completely discharged from the furnace with the flue gas. Only the high-temperature resistant nano-titanium-silicon composite active particles remain on the surface of the melt, precisely acting on the dense foam film on the surface of the molten glass.
[0073] In some embodiments, for a 1200-ton / day ultra-clear photovoltaic glass melting furnace, the daily usage of water-based defoamer is 500kg~800kg, which can be dynamically adjusted according to the furnace operating status: under high-load production and high foam production conditions, the daily usage is controlled at 700kg~800kg; under normal production load and low foam production conditions, the daily usage is maintained at 500kg~700kg. For melting furnaces of other tonnages, the dosage can be calculated proportionally based on the total melting volume of the glass batch.
[0074] Using the defoamer of this invention can effectively reduce the thickness of the foam layer, significantly lower the temperature at the top of the glass, reduce the temperature in areas with dense foam by approximately 44°C, increase the temperature at the bottom of the glass, and increase the effective thermal radiation of natural gas combustion heat to the molten glass, resulting in a 2.0% to 3.5% reduction in unit heat consumption. Simultaneously, the foam-covered area is significantly reduced, releasing more effective heat conduction area, achieving continuous energy saving and consumption reduction in large-scale mass production while efficiently eliminating foam.
[0075] In summary, the water-based defoamer prepared according to the present invention can effectively eliminate foam, reduce the crown temperature, increase the bottom temperature, and release the effective heat conduction area when used in large photovoltaic kilns, thereby achieving the goals of energy saving, consumption reduction, production cost saving, and kiln protection.
[0076] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0077] Example 1 This embodiment provides an aqueous defoamer, which is calculated based on a total mass of 100 parts. The raw material composition is as follows: 8 parts tetraisopropyl titanate, 4 parts methyltrimethoxysilane, 8 parts complexing agent (acetylacetone and ethylene glycol are compounded in a mass ratio of 1:1), 1 part polyacrylate, and the balance is deionized water (conductivity ≤10μS / cm), which is made up to 100 parts.
[0078] The preparation method of the water-based defoamer in this embodiment is as follows: Complexation reaction: Tetraisopropyl titanate and the compound complexing agent were put into a closed reaction vessel with stirring and temperature control functions, heated to 35°C, and stirred continuously at a constant temperature for 100 min to carry out the complexation reaction. Then, methyltrimethoxysilane was added and mixed evenly to obtain the complexed modified precursor.
[0079] Co-hydrolysis and condensation reaction: The temperature of the complex-modified precursor was controlled at 45℃, and deionized water was added dropwise to the reaction system at a stirring speed of 150 rpm for 45 min. After the addition was completed, the reaction was carried out at a constant temperature with continuous stirring for 45 min to obtain the titanium-silicon composite sol intermediate.
[0080] Dispersion and filtration: The titanium-silicon composite sol intermediate was heated to 55°C at a rate of 1.5°C / min, polyacrylate was added, and the stirring speed was adjusted to 300 rpm, and stirring was continued for 35 min. Then, it was precisely filtered through a 0.22 μm filter, and the filtrate was collected, sealed and stored to obtain the water-based defoamer.
[0081] Example 2 This embodiment provides an aqueous defoamer, which is calculated based on a total mass of 100 parts. The raw material composition is as follows: 7 parts tetraisopropyl titanate, 5 parts methyltrimethoxysilane, 7 parts complexing agent (acetylacetone and ethylene glycol are compounded in a mass ratio of 1:1), 1 part polyacrylate, and the balance is deionized water (conductivity ≤10μS / cm), which is made up to 100 parts.
[0082] The preparation method in this embodiment is basically the same as that in Example 1, except that the raw material ratio is different.
[0083] Example 3 This embodiment provides an aqueous defoamer, which is calculated based on a total mass of 100 parts. The raw material composition is as follows: 7 parts tetraisopropyl titanate, 3 parts methyltrimethoxysilane, 6 parts complexing agent (acetylacetone and ethylene glycol are compounded in a mass ratio of 1:1), 2 parts polyacrylate, and the balance is deionized water (conductivity ≤10μS / cm), which is made up to 100 parts.
[0084] The preparation method of this embodiment is basically the same as that of Example 1, except that the raw material ratio is different and the amount of water-based dispersant stabilizer is increased to 2 parts.
[0085] Comparative Example 1 This comparative example provides a traditional titanium powder defoamer, using commercially available nano titanium dioxide powder, with a solid content of 2.0-3.0% as a reference, which is added after dispersion.
[0086] Comparative Example 2 This comparative example provides a solvent-based titanium defoamer, which uses tetrabutyl titanate as the active component and aviation kerosene as the dispersion medium, and is prepared by mixing them at a mass ratio of 1:5.
[0087] Performance testing 1. The defoamers prepared in Examples 1 to 3 were subjected to physicochemical property tests, and the test results are shown in Table 1.
[0088] 2. The nanoparticle size (nm) of the defoamers obtained in Examples 1-3 was detected using dynamic light scattering (DLS), and the results are shown in [Figure number missing]. Figure 2 .
[0089] Depend on Figure 2 It can be seen that the nanoparticles in the aqueous defoamers of Examples 1 to 3 all have a particle size between 1 nm and 30 nm and good dispersibility.
[0090] Among them, Example 1, due to its higher proportion of titanate, had a more dispersed particle size distribution compared to Examples 2 and 3. Example 2, with its increased proportion of silane coupling agent, had a more concentrated particle size distribution, with a peak value of 6.91 nm. Example 3, with its most concentrated defoamer particle size distribution and a peak value of 5.04 nm, was the best among the three groups.
[0091] In addition, increasing the amount of aqueous dispersant stabilizer can further prevent the aggregation of nanoparticles during hydrolysis and improve the stability of the system.
[0092] Table 1. Physicochemical properties of defoamers in different embodiments
[0093] Application example: Defoaming experiment in a large photovoltaic kiln Experiments were conducted on the use of defoamers in a large-scale photovoltaic kiln with a capacity of 1200T / d domestic.
[0094] Specifically, the defoamers prepared in Examples 1 to 3, Comparative Examples 1 and 2 were used at a dosage of 750 kg / d. They were directly sprayed onto the foam accumulation area on the surface of the molten glass inside the furnace. Changes in parameters such as glass composition, furnace temperature, energy consumption, and yield were tested before and after use. The following experimental data are selected from before and one week after the use of the defoamer.
[0095]
[0096] From Table 2, we can see that: The water-based defoamers in Examples 1 to 3 showed no significant changes in the glass composition before and after use, indicating that the use of the defoamers of the present invention does not affect the glass composition.
[0097] Comparative Example 1 used commercially available nano titanium dioxide powder for dispersion, which also had no significant effect on the glass composition.
[0098] Comparative Example 2 used tetraisobutyl titanate as the active component and aviation kerosene as the dispersion medium. Accompanied by natural gas combustion, only titanium dioxide acted on the glass melt, and it also had no significant effect on the glass composition.
[0099]
[0100] From Table 3, we can see that: In Examples 1-3, the temperature at the top of the glass decreased significantly after using water-based defoamer. The temperature in the foam-dense areas (furnaces #5 and #6) decreased by 37-44°C, while the temperature at the bottom of the glass increased to varying degrees (6°C-19°C). This indicates that the use of defoamer effectively eliminated the thickness of the foam layer and significantly increased the effective thermal radiation of natural gas combustion heat to the molten glass.
[0101] Comparative Example 1, due to the direct use of nano-titanium dioxide powder dispersion, exhibited visible agglomeration during use. After being sprayed above the molten glass, the temperature at the top of the arch decreased slightly, and the effect was significantly worse than that of the water-based defoamers in Examples 1-3.
[0102] In Comparative Example 2, after aviation kerosene is burned with natural gas, the tiny titanium dioxide particles have a defoaming effect, but the effect is slightly worse than that of the water-based defoamers in Examples 1-3.
[0103]
[0104] From Table 4, we can see that: In Example 3, the unit heat consumption decreased by 3.03% after using the defoamer (from 1387 kcal / kg to 1345 kcal / kg), and the foam coverage area was reduced from furnace #9 to furnace #7, freeing up the effective heat conduction area of the two pairs of furnaces. Meanwhile, the use of the defoamer did not significantly affect the glass yield or glass transmittance. Both Examples 1 and 3 achieved good defoaming effects.
[0105] Comparative Example 1 showed lower reductions in unit heat consumption and effective foam reduction area compared to the water-based defoamers in Examples 1-3, and the transmittance of the glass after defoaming was lower than before defoaming.
[0106] Comparative Example 2 showed lower reductions in unit heat consumption and effective foam reduction area compared to the water-based defoamers in Examples 1-3, and the transmittance of the glass after defoaming was lower than before defoaming.
[0107] In summary, the defoamer prepared according to the present invention can effectively eliminate foam, reduce the crown temperature, increase the bottom temperature, and release the effective heat conduction area when used in large photovoltaic kilns, thereby achieving the goals of energy saving, consumption reduction, production cost saving, and kiln protection.
[0108] Stability test The defoamer prepared in the examples was stored in a light-proof and cool environment at 25±2℃. After being stored for 0, 30, 90 and 180 days from the date of preparation, it was used for defoaming experiments. The appearance of the defoamer was observed to see if there was any layering, precipitation, oil floating, or color change.
[0109] The results are shown in Table 5.
[0110]
[0111] As shown in Table 5, the defoamer prepared in the embodiments of the present invention did not show any stratification, precipitation, oil floating, or color change even after being placed for 180 days. The average particle size was less than 30 nm, and the stability was very good.
[0112] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural or procedural transformations made based on the description and drawings of the present invention, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.
Claims
1. A water-based defoamer, characterized in that, The aqueous defoamer includes nanoparticles with a particle size range of 1 nm to 30 nm, and the nanoparticles contain Ti–O–Si covalent bonds; The nanoparticles are obtained by reacting titanate, silane coupling agent, complexing agent, and deionized water. The complexing agent includes at least one of acetylacetone, triethanolamine, diethanolamine, ethylene glycol, propylene glycol, and diethylene glycol. The titanate and the complexing agent undergo a complexation reaction to obtain a complex. The complex and the silane coupling agent undergo a co-hydrolysis reaction in the presence of deionized water to produce titanium-containing hydrolysis products and silicon-containing hydrolysis products. The titanium-containing hydrolysis product and the silicon-containing hydrolysis product undergo a condensation reaction to obtain an aqueous defoamer containing the nanoparticles.
2. The aqueous defoamer according to claim 1, characterized in that, The general reaction formula for the complexation reaction is as follows: The general reaction formula for the hydrolysis reaction is as follows: The general reaction formula for the condensation reaction is as follows: The titanate refers to the titanium ester, where R is -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; Refers to the complexing agent, where n is an integer greater than 0 and less than or equal to 2; Refers to the complex; Referring to the silane coupling agent, It is -CH3 or -CH=CH2. It is -CH3 or -CH2CH3; Refers to the aforementioned deionized water; Refers to the titanium hydrolysis products; Refers to the silicon hydrolysis products mentioned above; Refers to the nanoparticles.
3. The aqueous defoamer according to claim 1, characterized in that, The titanate includes at least one of tetraisopropyl titanate, tetra-n-butyl titanate, and tetraisobutyl titanate. And / or, the silane coupling agent includes at least one of methyltrimethoxysilane, methyltriethoxysilane, or vinyltriethoxysilane.
4. The aqueous defoamer according to claim 1, characterized in that, Based on a total mass of 100 parts, the titanate ester comprises 7-15 parts, the silane coupling agent comprises 3-6 parts, the complexing agent comprises 5-15 parts, and the remainder is deionized water.
5. The aqueous defoamer according to claim 4, characterized in that, The aqueous defoamer also includes an aqueous dispersing stabilizer.
6. The aqueous defoamer according to claim 5, characterized in that, The aqueous dispersion stabilizer includes at least one of polyacrylate, sodium hexametaphosphate, sodium pyrophosphate, and polyvinylpyrrolidone; and / or, calculated by weight, the aqueous dispersion stabilizer is 1 to 3 parts.
7. A method for preparing an aqueous defoamer as described in any one of claims 1 to 6, characterized in that, The preparation method Includes the following steps: Complexation reaction: Titanate and complexing agent are mixed and stirred to react, and then silane coupling agent is added and mixed to obtain complexed modified precursor; Co-hydrolysis and condensation reaction: Deionized water was added dropwise to the complexed modified precursor, and a co-hydrolysis and condensation reaction was carried out under heating and stirring conditions to obtain an aqueous defoamer containing nanoparticles.
8. The method for preparing the aqueous defoamer according to claim 7, characterized in that, The temperature of the stirring reaction is 30℃~40℃, and the reaction time is 90min~120min; And / or, in the steps of the co-hydrolysis and condensation reaction, the reaction temperature of the co-hydrolysis and condensation reaction is 35℃~55℃.
9. The method for preparing the aqueous defoamer according to claim 7, characterized in that, The preparation method further includes the following steps: Dispersion: Add an aqueous dispersing stabilizer to the aqueous defoamer containing nanoparticles.
10. A defoaming method for use in glass manufacturing processes, characterized in that, Includes the following steps: During the glass melting stage, the water-based defoamer described in any one of claims 1 to 6 is sprayed onto the surface of the molten glass to defoam.